2021
DOI: 10.1101/2021.09.08.459384
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptional regulation of HSCs in Aging and MDS reveals DDIT3 as a Potential Driver of Dyserythropoiesis

Abstract: Myelodysplastic syndromes (MDS) are clonal hematopoietic stem cell (HSC) malignancies characterized by ineffective hematopoiesis with increased incidence in elderly individuals. Genetic alterations do not fully explain the molecular pathogenesis of the disease, indicating that other types of lesions may play a role in its development. In this work, we analyzed the transcriptional lesions of human HSCs, demonstrating how aging and MDS are characterized by a complex transcriptional rewiring that manifests as div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…To substantiate our findings, we generated RNA‐sequencing data from ERCC6L2 ‐deficient erythroid‐committed HSPCs and used an in silico approach to infer cell abundance at various stages of differentiation within our populations. Based on gene signatures derived from single‐cell RNA‐sequencing analysis of erythroid subtypes, 10 , 11 we performed CIBERSORTx deconvolution on our bulk RNA‐sequencing data sets. Our analysis revealed that ERCC6L2‐ KD and patient erythroid cells had higher proportions of polychromatic erythroblasts compared to Scramble (61.5% and 36.6% respectively), which were enriched instead for more mature subtypes, orthochromatic erythroblasts (39.4%) or reticulocytes (32.6%) (Figure 4A ; Figure S5A ).…”
Section: Resultsmentioning
confidence: 99%
“…To substantiate our findings, we generated RNA‐sequencing data from ERCC6L2 ‐deficient erythroid‐committed HSPCs and used an in silico approach to infer cell abundance at various stages of differentiation within our populations. Based on gene signatures derived from single‐cell RNA‐sequencing analysis of erythroid subtypes, 10 , 11 we performed CIBERSORTx deconvolution on our bulk RNA‐sequencing data sets. Our analysis revealed that ERCC6L2‐ KD and patient erythroid cells had higher proportions of polychromatic erythroblasts compared to Scramble (61.5% and 36.6% respectively), which were enriched instead for more mature subtypes, orthochromatic erythroblasts (39.4%) or reticulocytes (32.6%) (Figure 4A ; Figure S5A ).…”
Section: Resultsmentioning
confidence: 99%
“…The EIF2AK1 effector DDIT3 is overexpressed in SF3B1 WT MDS HSCs ( 38 ). DDIT3 overexpression delays the erythroid differentiation of MDS CD34 + cells by affecting the activation of erythroid transcriptional programs.…”
Section: Discussionmentioning
confidence: 99%
“…DDIT3 overexpression delays the erythroid differentiation of MDS CD34 + cells by affecting the activation of erythroid transcriptional programs. The inhibition of DDIT3 in CD34 + cells isolated from MDS patients with anemia restores proper erythroid differentiation ( 38 ). Our study showed that the activation of the EIF2AK1 pathway occurs in the later stages of erythroblast maturation, as SF3B1 MT -induced aberrant splicing primarily affected the function of terminally differentiated erythroblasts with the highest mitochondrial content.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence suggests that the heme-regulated EIF2AK1 kinase pathway affects erythropoiesis in health and disease. For example, EIF2AK1 effector DDIT3 is overexpressed in MDS hematopoietic stem and progenitor cells ( Berastegui et al, 2021 ), DDIT3 overexpression delays erythroid differentiation in CD34-positive cells from MDS patients, and EIF2AK1 inhibition increases expression of both mitochondrial heme biosynthesis enzymes and iron transporters, reversing SF3B1 mutation-induced arrest of erythroid differentiation in vitro ( Adema et al, 2022 ).…”
Section: What Is Ineffective Erythropoiesis?mentioning
confidence: 99%